Analysis Needs for Integrating Local Cultural Values in Reading and Writing Learning for Second Grade Students (Preliminary Study for Developing an Ethnopedagogy Module) - Margaretha, Yaroserai; Sutarsih, Cicih (International Conference on Elementary Education, 2025)
This study aims to analyze the needs for integrating Bandung local cultural values into reading and writing instruction for second-grade elementary school students as an initial step in developing an ethnopedagogy-based module. The research background stems from the low basic literacy skills found among second-grade elementary students in Cibogo, Lembang. Out of a total of 23 students, 3 students were unable to read, while several students still experienced difficulties in reading fluency, writing simple sentences, and using capital letters and punctuation marks. This condition is exacerbated by instruction that remains dominated by lecture methods and the use of teaching modules that are not contextual to local life and culture. This study employs a qualitative approach with a needs analysis method through interview and observation techniques involving teachers and second-grade elementary students as research subjects. The analysis focuses on identifying elements of Bandung local culture, including community social life, natural environmental conditions, natural products, regional arts, and traditions that are still alive in the Elementary School Bandung community and surrounding areas. Preliminary findings indicate that teachers have not yet developed teaching modules that connect Indonesian language material with students' local cultural context. In fact, the integration of ethnopedagogical values is considered to have the potential to strengthen basic literacy skills through meaningful, contextual learning rooted in students' cultural experiences. Therefore, the results of this study are expected to serve as a foundation for developing ethnopedagogy-based learning modules that integrate Bandung local culture to improve the reading and writing skills of second-grade elementary students.